Deactivation of mitochondrial complex I after hypoxia–ischemia in the immature brain - Stepanova, Anna (J Cereb Blood Flow Metab, 2018)
Mortality from perinatal hypoxic–ischemic (HI) brain injury reached 1.15 million worldwide in 2010 and is also a major factor for neurological disability in infants. HI directly influences the oxidative phosphorylation enzyme complexes in mitochondria, but the exact mechanism of HI-reoxygenation response in brain remains largely unresolved. After induction of HI-reoxygenation in postnatal day 10 rats, activities of mitochondrial respiratory chain enzymes were analysed and complexome profiling was performed. The effect of conformational state (active/deactive (A/D) transition) of mitochondrial complex I on H(2)O(2) release was measured simultaneously with mitochondrial oxygen consumption. In contrast to cytochrome c oxidase and succinate dehydrogenase, HI-reoxygenation resulted in inhibition of mitochondrial complex I at 4 h after reoxygenation. Immediately after HI, we observed a robust increase in the content of deactive (D) form of complex I. The D-form is less active in reactive oxygen species (ROS) production via reversed electron transfer, indicating the key role of the deactivation of complex I in ischemia/reoxygenation. We describe a novel mechanism of mitochondrial response to ischemia in the immature brain. HI induced a deactivation of complex I in order to reduce ROS production following reoxygenation. Delayed activation of complex I represents a novel mitochondrial target for pathological-activated therapy.